Membangun Ketahanan Sosial Masyarakat Menangani Tindak Kekerasan Seksual Terhadap Anak - Aziwarti Aziwarti; Afrizal Afrizal; Bob Alfiandi; Yulkardi Yulkardi; Azwar Azwar; Elfitra Elfitra; Maihasni Maihasni; Mira Elfina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2016)
Increasing acts of sexual violence committed against children is an event that is disturbing the public, especially to families with children of men and women. In this case needs special attention to children from parents, the community and government. Attention, awareness and community participation is essential to prevent acts of sexual violence against children . In Koto Baru Payakumbuh city that sexual violence is an aberration and society mention the term sudah tapijak arang means he already had one error that can not be forgiven and the penalty removed by the village . Another term of this crime panaaka jawi means same-sex sexual relations .